2005
DOI: 10.1300/j013v41n02_02
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Anthropometric Measurements of Idealized Females and Young Women in General

Abstract: This study examined the temporal anthropometric changes in idealized female body images in the media (i.e., Playboy magazine Playmates of the Year, Miss America Pageant winners, and fashion models) and young women in general across eight decades. Overall, all anthropometric measures differed significantly over time. BMI for all women in the idealized groups tended to decline significantly over time, while the BMI for YoungWomen increased significantly. Models tended to have the smallest bust and hips, Playmate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…Thus, differences in obesity prevalence appear to be less suited to explain gender differences in the underestimation of overweight and obesity. However, a substantial body of research does suggest that women, but not men, in developed countries are very frequently exposed to slender same‐sex bodies through popular media 102, 103, 104. Therefore, the tendency for women to be exposed to slender female bodies in the media may cause the perception of what constitutes a ‘normal’ female body size to be smaller than that of a ‘normal’ male body size 105 because of ‘internalization of thin ideals’.…”
Section: Social Patterning Of Personal Underestimation Of Overweight mentioning
confidence: 99%
“…Thus, differences in obesity prevalence appear to be less suited to explain gender differences in the underestimation of overweight and obesity. However, a substantial body of research does suggest that women, but not men, in developed countries are very frequently exposed to slender same‐sex bodies through popular media 102, 103, 104. Therefore, the tendency for women to be exposed to slender female bodies in the media may cause the perception of what constitutes a ‘normal’ female body size to be smaller than that of a ‘normal’ male body size 105 because of ‘internalization of thin ideals’.…”
Section: Social Patterning Of Personal Underestimation Of Overweight mentioning
confidence: 99%
“…The weight of idealized women in the media is extremely low (e.g., Byrd-Bredbenner, Murray, & Schlussel, 2005; Sypeck et al, 2006; Wiseman, Gray, Mosimann, & Ahrens, 1992), and coupled with these thin-ideal images comes the message that individuals who are thin are the most valued, loved, and successful (Hesse-Biber, Leavy, Quinn, & Zoino, 2006). Western culture has supported the notion that the extremely thin look is both desirable and achievable, when in fact, this ideal is very difficult for most women to achieve and maintain (Brownell, 1991).…”
mentioning
confidence: 99%
“…In other words, celebrities act as vicarious role models. Bredbenner, Murray, & Schlussel (2005) researched the idealized female body images in the media. They found that the media plays an important role in defining the "beautiful body".…”
Section: Role Modelsmentioning
confidence: 99%